(untitled) (Research, Society and Development, 2021)
This article aims to describe the main topics of approach of the research group Management of Professional Training and Qualification in the areas of teaching, research and extension, with a view to the professional qualification of students and professionals in the field of health. It is a proposal for an experience report, with a descriptive qualitative approach on the main themes of approach of the research group Management of Professional Training and Qualification in the areas of teaching, research and extension. This article is based on the following discussions: Open Researcher and Contributor ID, Participatory Action Research, Traditional Chinese Medicine, Scientific Publication, Pedagogical Practices for the Training of Health Professionals and Hybrid Learning in Higher Education. With a view to training and professional qualification in health, innovation is sought with the proposal to discuss relevant topics knowing the reality of its students and professionals. As a conclusion, it is understood the participative and reflective importance of an interdisciplinary training by competences capable of understanding the demands of the current world, considering an integral education of the subject in the health area.